Implementation of biogas-based energy security program and evaluation of its sustainability in Kediri village, Pringsewu district, Lampung province - Damayanti, Sri Ismiyati; Ginting, Simparmin; Nawansih, Otik; Hudaidah, Siti (ASEAN Journal of Community Engagement, 2020)
The Biogas-based energy security program in Kediri Village, Pringsewu District, Lampung Province, aims to provide awareness and knowledge to villagers about the potential of cow dung to be made into biogas and promote awareness of good environment quality. An evaluation of the sustainability of the program in the community was conducted. The methods that were used in this program are (1) socialization to provide awareness of good environment quality and energy security, (2) digester construction and stove and biogas lamp installation, which was carried out by the community together with certified trainers, (3) creation of a master design of the digester layout to ensure the maximum utilization of the digesters, and (4) evaluation to determine opportunities for program sustainability. Results show that the Biogas-based Energy Security Program has succeeded in making the community aware of and accept and apply the technology of processing cow manure into biogas. Biogas has met 100% of the fuel needs for cooking and electricity of biogas-fed houses. The environment quality has also improved, as shown by clean cages and home environments, and methane emissions have reduced. Over the five-year program, 11 out of 20 planned digesters have been built. The program's future sustainability can be continued by the community, provided that alternative sources of funds that can be pursued by the community are available.